Increase of temperature exacerbates the conversion of P fractions in organic horizon - Luo, Chaoyi; Wu, Yanhong; He, Qingqing; Wang, Jipeng; Bing, Haijian (Soil biology & biochemistry, 2024)
In terrestrial ecosystems, phosphorus (P) is the limiting nutrient of primary production. The soil organic horizon is a vital source of bioavailable P in subalpine coniferous forests. However, the response of organic horizon P to temperature increase in subalpine coniferous forests is not well characterized. By studying different decomposed degree of organic horizon across an altitudinal gradient, we aimed to simulate responses of the organic horizon P conversion to MAT increase in subalpine ecosystems. In this study, relative enrichment and relative depletion of P fractions were defined as the conversions between different P fractions. We initially observed only unidirectional conversion from labile inorganic P (LIP) to highly resistant organic P (HOP) at a mean annual temperature (MAT) of 1 °C. However, with increasing MAT, there was a relative depletion of moderately resistant inorganic P (MIP) (MAT = 2.4 °C), followed by a successive depletion of moderately resistant organic P (MOP) (MAT = 4.1 °C). Concurrently, we observed relative enrichment of labile organic P (LOP) (MAT = 2.4 °C). Combined with indoor incubation experiments, we further found that the concentration of available P peaked (81.79 mg kg−1) at the initial stage of MIP relative depletion (MAT = 2.4 °C), while the net P mineralization rate (2.19 mg kg−1 d−1) reached a maximum following the initial relative depletion of MOP (MAT = 4.1 °C). Under elevated temperature, the pH of the organic horizon plays a crucial role in determining P fractions variation. These findings suggest that temperature increase can exacerbate the conversion of P fractions and the release of bioavailable P from organic horizon by successively triggering the relative depletion of MIP, the relative enrichment of LOP and relative depletion of MOP at specific MAT thresholds, which has important implications for the enhancement of primary production and carbon sequestration in subtropical coniferous forests under future climate warming. •There was only a unidirectional conversion from LIP to HOP at a MAT of 1.0 °C.•As The MAT increased, MIP began to be released at a MAT of 2.4 °C, followed by degradation of MOP at a MAT of 4.1 °C.•As The MAT increased, LIP began to show significant enrichment at a MAT of 2.4 °C.•The concentration of AP exhibited a significant peak at the initial stage of MIP release at a MAT of 2.4 °C.•The net release rate of AP reached relative stability following the initial degradation of MOP at a MAT of 4.1 °C.